Metal-free annulation of β-acylamino ketones: facile access to spirooxazolines and oxazolines via oxidative C–O bond formation - Chavan, Santosh S.; Rupanawar, Bapurao D.; Kamble, Rohit B.; Shelke, Anil M.; Gurunath Suryavanshi (Organic Chemistry Frontiers, 2018)
A metal-free annulation reaction of β-acylamino ketone derivatives has been reported for the synthesis of a group of functionalized spirooxazolines and oxazolines in good to excellent yields. The reaction proceeds via phenyliodine(III) diacetate (PIDA)-mediated oxidative C–O bond formation in the presence of BF3–OEt2. The mild reaction conditions, broad substrate scope, simple execution and synthetic potential of the products make this novel protocol very attractive.

Oxidative Olefination of Benzylamine with an Active Methylene Compound Mediated by Hypervalent Iodine (III) - Rupanawar, Bapurao D.; Veetil, Sruthi M.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2019)
Hypervalent iodine-mediated oxidative olefination of amines with an active methylene compound provides a rapid gateway towards the formation of electrophilic alkenes under mild reaction conditions in good to excellent yields. This is an efficient protocol for the preparation of substituted electrophilic alkenes.

Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.

Hypervalent iodine(iii) induced oxidative olefination of benzylamines using Wittig reagents - Ramavath, Vijayalakshmi; Rupanawar, Bapurao D.; More, Satish G.; Bansode, Ajay H.; Suryavanshi, Gurunath (New Journal of Chemistry, 2021)
We have developed hypervalent iodine(iii) induced oxidative olefination of primary and secondary benzylamines using 2C-Wittig reagents, which provides easy access to alpha,beta-unsaturated esters. Mild reaction conditions, good to excellent yields with high (E) selectivity, and a broad substrate scope are the key features of this reaction. We have successfully carried out the gram-scale synthesis of alpha,beta-unsaturated esters.

Metal-free, acid-catalyzed 1,6-conjugate addition of NH-sulfoximines to para-quinone methides: accessing to diarylmethine imino sulfanone - More, Satish G.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
We have reported an efficient and metal-free method for the construction of alpha-diarylmethine imino sulfanone using acid-catalyzed 1,6-conjugate addition of sulfoximines on para-quinine methides (p-QMs). This method showed broad functional group tolerance and a wide range of substrate scope with good to excellent yield. The excellent protocol exhibits mild reaction conditions with high atom economy. The practicability of the present method was supported by a Gram-scale reaction.

Hypervalent-iodine-mediated oxidation followed by the acetoxylation/tosylation of alpha-substituted benzylamines to obtain alpha-acyloxy/tosyloxy ketones - Rupanawar, Bapurao D.; Mane, Kishor D.; Suryavanshi, Gurunath (New Journal of Chemistry, 2022)
An efficient and metal-free method has been developed for the sequential oxidation of alpha-alkylbenzylamines followed by acetoxylation or tosylation for the synthesis of alpha-acyloxy/tosyloxy ketones using hypervalent iodine(iii). The employment of a simple starting material, broad substrate scope and operational simplicity are the key features of this protocol.

Visible light-promoted, photocatalyst-free C(sp(2))-H bond functionalization of indolizines via EDA complexes - Mane, Kishor D.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2022)
The catalyst and additive-free, photo-driven cross dehydrogenative coupling (CDC) reaction initiated by electron donor-acceptor (EDA) complexes between electron rich indolizines and electron poor quinones has been demonstrated. This green transformation reveals the advantages of operational simplicity, mild reaction conditions and good functional group tolerances.
Keywords: Blue LED; CDC; EDA; Indolizine; Quinone

Hypervalent-iodine-mediated base-free oxidative olefination of benzylic amines to access α,β-unsaturated ketones - Rupanawar, Bapurao D.; Bansode, Ajay H.; Suryavanshi, Gurunath (Synlett, 2025)
We report a one-pot base-free protocol for the oxidative olefination of benzylic amines promoted by a hypervalent iodine reagent for the synthesis of alpha,beta-unsaturated ketones. Mechanistically, (diacetoxyiodo)benzene oxidizes the benzylic amine to the corresponding imine, which, on reaction with a phenacyl(triphenyl)phosphonium bromide salt and an in situ generated acetoxy anion leads to an alpha,beta-unsaturated ketone. A wide range of alpha,beta-unsaturated ketones were easily accessed through direct oxidative olefination of substituted benzylic amines in good to excellent yields and with high E -selectivity.
Keywords: benzylic amines; enones; hypervalent iodine; olefination; Oxidation